THE ROLE OF PARENTS IN INTRODUCING SEXUAL EDUCATION TO EARLY CHILDHOOD - Sufi Shohibul Wafa; Hayani Wulandari (Islamic EduKids: Jurnal Pendidikan Anak Usia Dini, 2024)
Abstract This study aims to determine the role of parents in introducing sexual education to early childhood. The research method used is the descriptive qualitative method. The instrument used in this research is a questionnaire distributed online to 30 parents of early childhood in one of the PAUD Kertamukti Cianjur Village. The results of this study indicate that parents' understanding of sexual education is still in the lower category, this is because there are still many parents who think that sexual education is taboo and inappropriate to introduce in early childhood. The role of parents in introducing sexual education to early childhood is as educators and companions. In general, the role of parents in introducing sexual education to children is very good. Parents already have an awareness of how important their role is in introducing sexual education to children from an early age, parents have begun to provide understanding, guidance, and direction to children regarding sexual education. Keywords:  role of parents, sexual education, early childhood.   Abstrak Penelitian ini bertujuan untuk mengetahui peran orang tua dalam mengenalkan pendidikan seksual kepada anak usia dini. Metode penelitian yang digunakan yaitu metode deskriptif kualitatif. Instrumen yang digunakan dalam penelitian ini yaitu kuisioner yang dibagikan secara online kepada 30 orang tua anak usia dini di salah satu PAUD Desa Kertamukti Cianjur. Hasil penelitian ini menunjukan bahwa pemahaman orang tua terhadap pendidikan seksual masih dalam kategori kurang, hal ini dikarenakan masih banyak orang tua yang beranggapan bahwa pendidikan seksual merupakan hal yang tabu dan tidak pantas untuk dikenalkan kepada anak usia dini. Peran orang tua dalam mengenalkan pendidikan seksual kepada anak usia dini yaitu sebagai pendidik dan pendamping. Secara umum peran orang tua dalam mengenalkan pendidikan seksual kepada anak sudah sangat baik. Orang tua sudah memiliki kesadaran tentang sebarapa penting peranannya dalam mengenalkan pendidikan seksual kepada anak sejak dini, orang tua sudah mulai memberikan pemahaman, bimbingan, dan pengarahan kepada anak mengenai pendidikan seksual. Kata Kunci: peran orang tua, pendidikan seksual, anak usia dini.